Evaluation of Biological Effective Dose in Gamma Knife Staged Stereotactic Radiosurgery for Large Brain Metastases - Cui, Taoran; Weiner, Joseph; Danish, Shabbar; Chundury, Anupama; Ohri, Nisha; Yue, Ning; Wang, Xiao; Nie, Ke (Frontiers in Oncology, 2022)
Abstract Objective: Gammaknife (GK) staged stereotactic radiosurgery (Staged-SRS) has become an effective treatment option for large brain metastases (BMs), however, it has been challenging to evaluate the total dose because of tumor shrinkage between two staged sessions. This study aims to evaluate total biological effective dose (BED) in Staged-SRS, and to compare the BED with those in single-fraction SRS (SF-SRS) and hypo-fractionated SRS (HF-SRS). Methods: Patients treated with GK Staged-SRS at a single institution were retrospectively included. The dose delivered in two sessions of Staged-SRS was summed using the deformable image registration. Each patient was replanned for SF-SRS and HF-SRS. The total BEDs were computed using the linear-quadratic model. Tumor BED98% ¬and brain V84Gy2, equivalent to V12Gy in SF-SRS, were compared between SF-SRS, HF-SRS, and Staged-SRS plans with the Wilcoxon test. Results: Twelve patients with 24 BMs treated with GK Staged-SRS were identified. We observed significant differences (p<0.05) in tumor BE¬D98% but comparable brain V84Gy2 (p=0.677) between the Staged-SRS and SF-SRS plans. No dosimetric advantages of Staged-SRS over HF-SRS were observed. Tumor BED98% in the HF-SRS plans was significantly higher than those in the Staged-SRS plans (p<0.05). Despite the larger PTVs, brain V84Gy2 in the HF-SRS plans remained lower (p< 0.05). Conclusion: We presented an approach to calculate the composite BEDs delivered to both tumor and normal brain tissue in Staged-SRS. Compared to SF-SRS, Staged-SRS delivers a higher dose to tumor but a comparable dose to normal brain tissue. Our results didn’t show any dosimetric advantages of Staged-SRS over HF-SRS.